ANALISIS PENGARUH DANA DESA TERHADAP TINGKAT KEMISKINAN DI SULAWESI TENGAH 2015 â€“ 2019 - Yanuar, Ananto; Anwar, Chairil; Jokolelono, Eko (Katalogis, 2021)
This study aims to determine the description of village funds on infrastructure spending, village funds for non-infrastructure spending, and local government spending in the education, health, empowerment of rural communities, capital expenditures, and their impact on poverty in Central Sulawesi. The background of this research is to see the contribution of village funds to poverty reduction according to the mandate of Law Number 6 of 2014. In addition, there is a literature gap regarding the effect of local government spending on education, health, empowerment of rural communities, and capital spending on poverty. There are no effect, a positive effect, and a negative effect.Â  The data used in this study came from raw data on Village Fund Realization from KPW VI, raw data for K-2 District / City Government Finance and other BPS publications. The time period analyzed was from 2015 to 2019. The unit of analysis used was 12 districts in Central Sulawesi. The findings show that village funds have changed the face of the village. Village funds have produced many infrastructure in the villages throughout 2015 to 2019, but based on the results of panel data regression analysis with the best model, the Random Effect Model (REM) shows that village funds both infrastructure and non-infrastructure spending have not been able to affect poverty levels, as well as local government spending on the education sector and regional government capital expenditures also have no effect on poverty levels. Meanwhile, local government spending in the health sector and the empowerment sector for rural communities has a negative effect on poverty levels.